1996
DOI: 10.1002/jlb.59.4.562
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen regulation of JE/MCP-1 mRNA expression in fibroblasts

Abstract: We have recently demonstrated that 17 beta-estradiol (E2) inhibits peritoneal adhesion formation. Because macrophages play a central role in inflammation and wound healing, we chose to investigate whether the E2 could inhibit the expression of JE, the murine monocyte chemoattractant protein-1 (MCP-1). To accomplish this, murine fibroblasts were cultured with physiological concentrations of E2 (3-300 pg/ml) with or without inducers of JE/MCP-1 mRNA expression. Untreated cells failed to express the message, but,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 29 publications
0
17
1
1
Order By: Relevance
“…AP-1 has recently been characterized as an antioxidant-responsive transcription factor. 32,33 Estradiolinduced decreases in MCP-1 mRNA expression 12,14 as well as increases in NO synthase expression 34 have been assumed to be mediated in part by estrogen receptor (ER)␣, because tamoxifen, an ER␣ receptor antagonist, attenuates these effects. However, it is possible that part of the effect of estradiol on the vessel wall may be mediated by the newly discovered ER␤, as it has recently been demonstrated that after carotid arterial injury in a mouse model in which the ER␣ gene is disrupted, estradiol inhibited vascular smooth muscle cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AP-1 has recently been characterized as an antioxidant-responsive transcription factor. 32,33 Estradiolinduced decreases in MCP-1 mRNA expression 12,14 as well as increases in NO synthase expression 34 have been assumed to be mediated in part by estrogen receptor (ER)␣, because tamoxifen, an ER␣ receptor antagonist, attenuates these effects. However, it is possible that part of the effect of estradiol on the vessel wall may be mediated by the newly discovered ER␤, as it has recently been demonstrated that after carotid arterial injury in a mouse model in which the ER␣ gene is disrupted, estradiol inhibited vascular smooth muscle cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…However, a direct inhibitory action of estradiol on MCP-1 production in macrophages has also been demonstrated by other investigators. [12][13][14]16 Potential mechanisms by which estradiol may inhibit MCP-1 expression must also be considered. For example, NO inhibits MCP-1 gene expression 27 and estradiol increases NO production in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies in animals show full atheroprotection at E2 doses that do not alter the lipid profile (2). Thus attention has focused on the direct effects of E2 on the vessel wall and on the processes involved in the inflammatory and fibroproliferative components of atherosclerosis including: endothelial permeability to LDL (10), LDL oxidation (11,12), cytokine and cell adhesion molecule expression (13)(14)(15)(16), macrophage cholesterol homeostasis (17), vascular smooth muscle cell and neointimal proliferation and migration (18,19), calcification (20,21) and platelet adhesion and aggregation (22).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, neither of the bone resorption inhibitory hormones, calcitonin or 17␤-estradiol, directly influenced either basal or IL-1␣-stimulated IL-8 release from hOCL, although hOCL expressed mRNA for each receptor and have responded in other ways to calcitonin (46) and 17␤-estradiol (47). Estrogen also does not affect basal or stimulated IL-8 release by hBMS, hOB, or human MG-63 osteosarcoma cells (19,48,49), although estrogen can inhibit cytokine-induced MCP-1 production in fibroblasts (50). Thus, hOCL production of IL-8 is predominantly regulated by inflammatory mediators and not by other osteotropic factors or hormones.…”
Section: Discussionmentioning
confidence: 89%